PENGARUH MOTIVASI BELAJAR TERHADAP HASIL BELAJAR MATA PELAJARAN HYGIENE DAN SANITASI PADA SISWA KELAS XI JURUSAN TATA KECANTIKAN DI SMK N 3 PAYAKUMBUH - Anggraini, Winda; Rostamailis, Rostamailis; Kasmita, Kasmita (Journal of Home Economics and Tourism, 2013)
This studyoriginatedfromthe factthatthe authorsfind at thefieldthatis stilla lack ofstudent motivationinlearningHygieneandSanitation, spiritandtenacityshownstudentsin learningHygiene andSanitationis lacking,studentsstilllovelazingin thestudy. The purposeof this studyaimsto describehowstudent motivation, student learning outcomesandthe influence ofmotivationon learning outcomes ofhygieneandsanitationsubjectsin classXIin theBeautyDepartmentSMKN 3 Payakumbuh. This research is(Ex PostFacto). Populationandthe samplewere students ofclassXIin theBeauty GovermaceDepartmentSMKN3Payakumbuhtakenas a wholewith 43 person. Data takenitemswith thestatementusinga Likert scaleof measurementscales. Motivationvariablesobtainedreliability fromCronbach's alphavalueis0.901whichlies inveryhighcondition. The data analysis techniqueusedisdescriptiveanalysis, testrequirements analysis, simpleregressionandhypothesis testing(t-test) .The results showed thatthere is apositiveand significantrelationship, betweenlearning motivation andlearning outcomes. Resultsof the analysis showedthat themotivationeffectof 18.8% of thesubjectslearning outcomesHygieneandSanitation, while81.2% is influencedbyothervariablesthatare notidentifiedin this study. Â  Kata Kunci :Adanya hasrat dan keinginan untuk berhasil, dorongan dan kebutuhan dalam belajar, harapan dan cita-cita masa depan, penghargaan dalam belajar, kegiatan yang menarik dalam belajar.